The Development of a Puzzle-Based Educational Game Using Roblox to Enhance Fundamental Python Commands Knowledge for Vocational Certificate Year 1 Students - บรรจงเก็บ เสฏฐนันท์; งามละม้าย ศุภโชค; เดชกูญชร ธนดล; เดชกูญชร ธนดล; ศุภัคธัญญากิจ โกเมศ; พ่วกำเหนิด สุพจน์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) develop a game-based learning environment utilizing puzzle and obstacle (Obby) mechanics on the Roblox platform, covering fundamental Python programming for first-year vocational certificate students; 2) evaluate the system’s quality and performance by experts; and 3) investigate student satisfaction. The sample, selected through purposive sampling, consisted of 3 experts in computer and digital media, and 35 first-year vocational students in the Digital Business Technology program at Siam Business Administration Technological College, Saphan Mai Campus, during the second semester of the 2025 academic year. Research instruments included the "Python Obby" game-based learning environment, a system quality assessment form, and a satisfaction questionnaire. Data were analyzed using mean and standard deviation. The results revealed that: 1) The developed game-based learning environment successfully integrated game mechanics with scaffolding theory and immediate feedback to reduce the cognitive load associated with learning complex programming syntax. 2) The system’s quality and performance, evaluated by experts, were at the highest level of suitability (Mean = 4.61, S.D. = 0.49), indicating high practical stability. 3) Overall student satisfaction was at a high level (Mean = 3.99, S.D. = 1.35). The findings suggest that integrating Flow Theory within a 3D virtual platform can shift the computer science pedagogy from abstract concepts to concrete experiences, effectively promoting active learning and intrinsic motivation among students.